Input‐based Stress Management Fails to Increase Soybean Yield in Kentucky. Issue 1 (12th November 2015) - Gregg, Gary L.; Orlowski, John M.; Lee, Chad D.
Abstract : Soybean producers have recently adopted management systems that attempt to manipulate plant stress throughout the growing season in an effort to increase yield. The purpose of this study was to determine if management systems that utilize crop inputs to manipulate soybean stress can increase soybean seed yield. Inputs designed to affect soybean stress were applied to early‐maturity (2.8 relative maturity [RM]) and full‐season (4.5 RM) soybean at three locations in Kentucky throughout the 2013 and 2014 growing seasons. Treatments consisted of a single application, sequential applications, or combined applications of the following inputs: lactofen, lambda‐cyhalothrin with thiamethoxam, pyraclostrobin, and N, N'‐diformyl urea. The full‐season soybean yielded greater (19%) than the early‐season soybean, resulting from an increase in mainstem node, pod, and seed numbers. Lactofen decreased early season light interception in all environments but did not affect soybean yield. None of the stress‐management inputs investigated increased yield compared to untreated soybeans. Soybean stress management through prophylactic input application does not appear to be a viable strategy to increase soybean yield.